Astrogliosis releases pro-oncogenic chitinase 3-like 1 causing mapk signaling in glioblastoma - Wurm, Julian; Behringer, Simon P.; Ravi, Vidhya M.; Joseph, Kevin; Neidert, Nicolas; Maier, Julian P.; Doria-Medina, Roberto; Follo, Marie; Delev, Daniel; Pfeifer, Dietmar; Beck, Jürgen; Sankowski, Roman; et al. (Cancers, 2019)
Although reactive astrocytes constitute a major component of the cellular environment in glioblastoma, their function and crosstalk to other components of the environment is still poorly understood. Gene expression analysis of purified astrocytes from both the tumor core and non-infiltrated cortex reveals a tumor-related up-regulation of Chitinase 3-like 1 (CHI3L1), a cytokine which is related to inflammation, extracellular tissue remodeling, and fibrosis. Further, we established and validated a co-culture model to investigate the impact of reactive astrocytes within the tumor microenvironment. Here we show that reactive astrocytes promote a subtype-shift of glioblastoma towards the mesenchymal phenotype, driving mitogen-activated protein kinases (MAPK) signaling as well as increased proliferation and migration. In addition, we demonstrate that MAPK signaling is directly caused by a CHI3L1-IL13RA2 co-binding, which leads to increased downstream MAPK and AKT signaling. This novel microenvironmental crosstalk highlights the crucial role of non-neoplastic cells in malignant brain tumors and opens up new perspectives for targeted therapies in glioblastoma.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Astrogliosis; CHI3L1; Glioblastoma microenvironment